2011
DOI: 10.1002/adfm.201002373
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐Selective Light‐Induced Release from Plasmon Resonant Liposomes

Abstract: Biodegradable, spectrally tunable plasmon resonant nanocapsules are created via the deposition of gold onto the surface of 100 nm diameter thermosensitive liposomes. These nanocapsules demonstrate selective release of encapsulated contents upon illumination with light of a wavelength matching their distinct resonance bands, which correspond to 760 and 1210 nm in this study. Spectrally selective release is accomplished through the use of multiple, low intensity laser pulses delivered over a period of less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 64 publications
(61 reference statements)
3
83
0
1
Order By: Relevance
“…(DSPC:DPPC), or 80:20 (DPPC:Chol), were tethered with AuNPs up to 132 ng/mL for exploring the optimal photoresponsive liposome for the fiber-optic guided laser triggered release study. 17,26,27,[39][40][41][42] The 90:10:4 (DPPC:MPPC:DSPEPEG2k) liposome with 33 ng/mL AuNPs achieved the strongest photo-thermal conversion efficiency while maintaining decent liposome integrity at physiological temperature without causing significant leakage (21.92%±2.08% in 40 minutes without excitation) as shown in Figure 6. The AuNP-incorporated liposomes were spherical in shape with AuNPs appearing as black dots floating on the surface, and had a uniform particle size distribution, primarily around 100 nm, as observed by TEM ( Figure 4B).…”
Section: Photo-thermal Energy Conversion Efficiency Of Aunps In Vitromentioning
confidence: 89%
See 1 more Smart Citation
“…(DSPC:DPPC), or 80:20 (DPPC:Chol), were tethered with AuNPs up to 132 ng/mL for exploring the optimal photoresponsive liposome for the fiber-optic guided laser triggered release study. 17,26,27,[39][40][41][42] The 90:10:4 (DPPC:MPPC:DSPEPEG2k) liposome with 33 ng/mL AuNPs achieved the strongest photo-thermal conversion efficiency while maintaining decent liposome integrity at physiological temperature without causing significant leakage (21.92%±2.08% in 40 minutes without excitation) as shown in Figure 6. The AuNP-incorporated liposomes were spherical in shape with AuNPs appearing as black dots floating on the surface, and had a uniform particle size distribution, primarily around 100 nm, as observed by TEM ( Figure 4B).…”
Section: Photo-thermal Energy Conversion Efficiency Of Aunps In Vitromentioning
confidence: 89%
“…Because of their proven biocompatibility and efficient photo-thermal conversion through surface plasma resonance, AuNPs (cluster, nanoshell) have previously been deposited on the liposome membrane outer surface, tethered to the liposome membrane, or entrapped within the liposome cavity for remotely triggered content release through wavelength-specific light excitation from the ultraviolet to near infrared region. [39][40][41][42] However, no studies have reported their corresponding content release efficiencies triggered by light excitation in vivo. This may be due to challenges caused by the inconsistent results of in vivo non-invasive irradiation from varying subject/disease conditions (such as tumor size and location).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] While most of them focus on the novelty of materials, accessibility and scalability issues need to be addressed. Moreover, reports on release mechanisms using these nanocarriers are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Gold liposomes were developed by the reduction of gold chloride onto the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) liposome surface following a previously reported method [21]. As shown in Table 1, gold liposomes showed a hydrodynamic size around 103 nm, and uncoated liposomes were around 92 nm.…”
Section: Preparation and Characterization Of Gold Liposomesmentioning
confidence: 99%